Color-changing fiber dressing and preparation method thereof

Through the combination of blended thread and curcumin color changer and AgNPs dip coating method, the problems of single and non-degradable wound dressing are solved, and multifunctional dressings with biocompatibility, degradability and color change indicator functions are realized, improving the The accuracy and environmental friendliness of wound healing monitoring are carried out.

CN119139527AInactive Publication Date: 2024-12-17SHANGHAI JINGHAIWEIXIANG BIOMATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411667984.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing wound dressing has a single function, making it difficult to accurately monitor wound healing, and traditional materials are not degradable, resulting in environmental pollution.

Method used

The blend of poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) was used to blend the wire, and curcumin was added as the color changer, and the antibacterial properties were enhanced by AgNPs dip coating. Color-discolored fiber dressings with biocompatible, degradability and color-discolored indication functions were prepared.

Benefits of technology

It realizes the multifunctionalization of wound healing monitoring, ensures the safety and environmental friendliness of the dressing, provides more effective wound care methods, and is simple and operational in the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119139527A_ABST
    Figure CN119139527A_ABST
Patent Text Reader

Abstract

The invention discloses a color-changing fiber dressing and a preparation method thereof, and belongs to the field of composite fiber dressings. Aiming at the problems that an existing wound dressing is single in function and is not beneficial to observation of wound conditions, the invention provides the preparation method of the color-changing fiber dressing, and the preparation method comprises the following steps: dissolving a polymer formed by poly (3-hydroxybutyrate) and poly (3-hydroxycaprylate-co-3-hydroxydecanoate) in a mixed solvent to obtain a polymer spinning solution; curcumin is added into the polymer spinning solution; the mixed solvent is a mixture of chloroform and dibutanol; and carrying out electrostatic spinning on the polymer spinning solution to obtain the color-changing fiber dressing. The dressing provided by the invention has good biological activity, biocompatibility, degradability, antibacterial property and color change indication function, realizes multifunctionalization, provides a new effective means for monitoring wound healing, and greatly improves the combination of wound dressing products, and the whole preparation method has simple steps and strong operability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite fiber dressings, and more specifically, relates to a color-changing fiber dressing and a preparation method thereof. Background Art

[0002] The wound healing process is a complex biological process involving the interaction of multiple cells and molecules. Traditional wound dressings mainly protect wounds, prevent infection and promote wound healing, but it is difficult to monitor the degree of wound healing. Doctors need to judge the healing status by observing the appearance, touch and possible exudate of the wound. This method not only relies on the doctor's experience, but is sometimes difficult to judge accurately. In the process of uncovering the dressing to observe the degree of wound healing, it may also cause secondary damage to the wound, which increases the workload of medical staff. In the process of chronic wound healing, pH value is considered to be the most decisive marker. Wound exudate increases the pH value of the wound from the normal slightly acidic 4.80-5.70 to above 7.4. The pH value of healthy skin is usually weakly acidic (pH=4.80-5.70). However, when the skin forms a wound, the pH value is weakly alkaline (pH=7.5-8.7). Therefore, pH sensitive materials can be used in dressings to monitor the pH value of the wound to understand the healing status of the wound. Based on this property, color-changing fiber materials can be applied to wound dressings, and drug-loaded fiber materials based on pH color change to indicate the wound can be designed. This makes it convenient for patients and doctors to monitor the infection without changing the dressing, avoiding bacteria from taking advantage of the opportunity to enter when the bandage is removed. The wound healing stage and bacterial infection status can be understood simply by observing the changes in the color of the dressing, which is conducive to guiding rational use of drugs.

[0003] Curcumin is a plant polyphenol extracted from turmeric and is also the most important active ingredient in turmeric that exerts pharmacological effects. It is a new type of natural pH indicator dye. As the pH value of the solution increases, the maximum absorption wavelength of the curcumin extract moves toward the long-wave direction. When it encounters an alkaline solution, it can change from yellow to red. Curcumin has antibacterial, anti-inflammatory and antioxidant effects. Pan (Pan N, Qin J, Feng P, Li Z, Song B. Color-changing smart fibrous materials for naked eye real-time monitoring of wound pH [J]. Journal of Materials Chemistry B, 2019, 7: 2626-2633.) et al. used electrospinning to load curcumin nanofiber membranes to monitor wound healing in situ in real time. The results showed that the curcumin-loaded fiber membrane showed obvious color changes from yellow to reddish brown at pH values ​​from 6.0 to 9.0, which can be easily detected by the human eye. However, the color stability of curcumin is affected by the external environment, resulting in relatively poor stability and biocompatibility. At the same time, traditional wound dressings use non-degradable materials such as polyester fibers and are usually not recycled - they are either incinerated or landfilled, causing environmental pollution.

[0004] Corresponding improvements have also been made to the above problems, such as China Patent Application No. CN202211011534.5, published on January 31, 2023. The patent discloses a gelatin / polyester fiber dressing and a preparation method thereof. The gelatin / polyester fiber dressing is composed of ultrafine fibers with a diameter of 300-1500nm, contains a pH indicator, can achieve visual color change in the pH range of 5-9, and has good cell compatibility. The preparation method of the gelatin / polyester fiber dressing is to dissolve polyester and curcumin in a mixed solvent composed of chloroform and N,N-dimethylformamide as a polyester spinning solution, dissolve gelatin in a trifluoroethanol solvent as a gelatin spinning solution, and co-electrospin the polyester spinning solution and the gelatin spinning solution to obtain a gelatin / polyester fiber dressing. The disadvantage of this patent is that the extraction and processing costs of gelatin may be high.

[0005] Another example is Chinese patent application number CN202310376251.9, published on July 21, 2023. The patent discloses a pH-sensitive chronic wound medical dressing with a unidirectional liquid guide function and a preparation method thereof. The anti-inflammatory and antioxidant properties of curcumin are used for targeted treatment of chronic wounds, and the physical and chemical environment of the wound is characterized by anthocyanin preparation. When the wound changes from an acidic pH value to an alkaline pH value, one of the two phenol groups is deprotonated to form a phenoxide ion, which is then stabilized by electron redistribution to form a ketone. The present invention controls the thickness of each layer of the film by controlling the electrospinning time, so that it has good unidirectional liquid guide properties. While being able to intuitively reflect the wound healing state, it can also prevent excessive hydration of the wound, thereby accelerating the wound healing process and avoiding further deterioration. The shortcomings of this patent are that the control process requirements for the thickness of each layer of the film are high, the overall preparation cycle is long and the cost is high. Summary of the invention

[0006] 1. Problems to be solved In view of the problem that existing wound dressings have a single function and are not conducive to observing the wound condition, the present invention provides a color-changing fiber dressing and a preparation method thereof. The dressing of the present invention has good biological activity, biocompatibility, degradability, antibacterial properties and color-changing indication function, realizes multifunctionality, provides a new and effective means for monitoring wound healing, and will greatly improve the combination of wound dressing products. The entire preparation method has simple steps and strong operability.

[0007] 2. Technical solution To solve the above problems, the present invention adopts the following technical solutions.

[0008] A method for preparing a color-changing fiber dressing comprises the following steps: S1: dissolving a polymer formed by poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) in a mixed solvent to obtain a polymer spinning solution; adding curcumin to the polymer spinning solution; the mixed solvent is a mixture of chloroform and dibutanol; S2: Electrospinning the polymer spinning solution to obtain a color-changing fiber dressing.

[0009] By adopting the above technical scheme, by utilizing the good biodegradability and biocompatibility of poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate), the impact on the environment can be reduced while ensuring compatibility with the skin, reducing the risk of allergies and irritation, and ensuring safety, which will greatly improve the disadvantages of traditional dressings; at the same time, by blending poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) with a low glass transition temperature with poly(3-hydroxybutyrate) with a high glass transition temperature, it is possible to produce fibers with better morphology and more stable performance in the subsequent electrospinning process, thereby meeting the dual requirements of wound dressings for material strength and flexibility; and the use of the two raw materials can broaden the color change range of the color-changing fiber, making the subsequent color change more intuitive and obvious; finally, by adding curcumin to the polymer, curcumin is used as a color-changing agent, so that the dressing can have a color-changing function, providing doctors and patients with an intuitive indication of the healing progress.

[0010] The entire preparation process is simple and easy to operate. The prepared color-changing fiber dressing can change color as the wound heals during wound care. It also has multiple functions such as biocompatibility, degradability, antibacterial properties, and color change indication, providing a new and effective means for monitoring wound healing, and has broad application prospects. Furthermore, in step S1, the mass ratio of poly(3-hydroxybutyrate) to poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) in the polymer is 1:(3-5); and the volume ratio of chloroform to dibutanol in the mixed solvent is (7-10):3.

[0011] By adopting the above technical solution, the mass ratio of the two raw materials is controlled. Since poly(3-hydroxybutyrate) has high strength and thermal stability, and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) has low glass transition temperature and high elasticity, controlling the ratio within a certain ratio can optimize the fiber performance and ensure that the processed fiber has good strength and toughness as well as good elasticity. By controlling the volume of chloroform and dibutanol in the mixed solvent, the appropriate solvent ratio can ensure that the fiber maintains a stable shape during the spinning process and reduce fiber defects caused by uneven solvent volatilization; at the same time, it avoids the waste of resources and saves costs.

[0012] Furthermore, in step S1, the weight ratio of the curcumin to the polymer spinning solution is (1-10):1.

[0013] By adopting the above technical scheme, considering that the stability of curcumin is easily disturbed by the environment, the response sensitivity of the fiber to environmental factors such as light and temperature is regulated by precisely controlling the amount of curcumin added, thereby achieving a richer color change effect and more precise color change control; and the addition of curcumin may also have a certain effect on the physical properties of the fiber, so avoiding the addition of excessive curcumin to affect the decline of fiber performance, and avoiding the addition of excessive curcumin to cause potential biological toxicity or allergic reactions, thereby ensuring the safety of the entire dressing.

[0014] Furthermore, the method further comprises step S3: modifying the color-changing fiber dressing by using the AgNPs dip-coating method to obtain the color-changing fiber dressing with antibacterial properties.

[0015] By adopting the above technical scheme, the color-changing fiber dressing is modified by the excellent antibacterial effect of silver nanoparticles in the AgNPs dipping method, so that the color-changing fiber dressing has antibacterial function, making wound care more efficient and safer; at the same time, the antibacterial properties of silver nanoparticles and the metal-enhanced singlet oxygen effect are utilized in the AgNPs dipping method to enhance the singlet oxygen production of curcumin, thereby producing a synergistic antibacterial effect and improving the stability of curcumin.

[0016] Furthermore, the AgNPs dip coating method specifically includes: using a 4000ppm colloidal silver aqueous solution to dip coat the color-changing fiber dressing for modification, the size of the nanosilver particles in the colloidal silver aqueous solution is 10-80nm; and the speed of taking the color-changing fiber dressing out of the colloidal silver aqueous solution is 170 mm / min.

[0017] Furthermore, before performing step S2, the method further includes adding LiBr solution after adding curcumin to the polymer spinning solution; and the added amount of the LiBr solution is 0.002 g / mL.

[0018] By adopting the above technical scheme, the addition of LiBr solution improves the conductivity of the entire polymer spinning solution, thereby promoting charge transfer during subsequent electrospinning and improving the spinning efficiency; and the addition of LiBr solution can make the electric field distribution of the polymer spinning solution more uniform, reduce the unstable factors in the spinning process, and then ensure the stability of spinning.

[0019] Furthermore, in step S2, the parameters of the electrospinning process are set as follows: the electrostatic voltage is 40-50 kV; the electrostatic field environment temperature is 22±1.6°C, the humidity is 38±2.1%, and the injection speed is 0.2-0.8 mL / h.

[0020] A color-changing fiber dressing is prepared by the method for preparing a color-changing fiber dressing as described in any one of the above items, and the color-changing fiber dressing has a thickness of 100-200 μm and a diameter of 300-2000 nm.

[0021] By adopting the above technical solution, the color-changing fiber dressing ensures its applicability and effectiveness in wound care; and it has good bioactivity, biocompatibility, biodegradability, antibacterial and color-changing properties, providing a more effective and safe means for wound monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the process of the present invention; Figure 2 The fiber membrane under different pH conditions Value (n=3); Figure 3 This is a graph showing the in vitro cytotoxicity experiment of PHA / nanosilver / curcumin fiber membranes with different curcumin contents. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with specific embodiments and drawings.

[0024] It should be explained here that the skin, as the largest organ of the human body, has the function of regulating body temperature and resisting the invasion of various pathogens and microorganisms. It is a natural barrier for direct contact between the human internal environment and the outside world. Therefore, the integrity of the skin is very important to human health. Wounds can be caused by damage and destruction of skin tissue, and many accidents in daily life can easily lead to wounds. The recovery process of the skin after trauma is dynamic and complex, including four stages: hemostasis, inflammation, cell proliferation and remodeling. According to the different recovery time of the wound, the wound can be divided into acute and chronic. For chronic wounds, the recovery time is long and the risk of exogenous negative interference is high. In order to protect the wound from external contamination, avoid wound deterioration, and promote wound healing, the use of wound dressings is the key to wound treatment.

[0025] Meanwhile, PHAs have been widely studied for their applications in biomedical fields, including drug delivery, wound healing, vascular grafts, orthopedic applications, and urological stents. PHAs containing 3–5 carbon atoms, such as poly(3-hydroxybutyrate) (P(3HB)) and poly(4-hydroxybutyrate) (P(4HB)), are considered short-chain length PHAs (scl-phas). Medium-chain length PHAs (mcl-phas) ​​contain 6–14 carbon atoms and include homopolymers such as poly(3-hydroxyhexanoate), P(3HHx), poly(3-hydroxyoctanoate), P(3HO), and heteropolymers such as P(3HHx-co-3HO). Scl-phas generally have higher molecular weights, higher crystallinity, and are brittle, whereas mcl-phas are more elastic. mcl-phas and their copolymers are the first choice for biomedical applications that require flexible biomaterials, such as heart valves or controlled drug delivery. The structural diversity of mcl-pha is higher than that of scl-pha and can therefore be easily designed as desired, since the monomer content of PHAs affects their physical and chemical properties. Figure 1 As shown, the present application provides a method for preparing a color-changing fiber dressing, which comprises the following steps: S1: dissolving a polymer formed by poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) in a mixed solvent to obtain a polymer spinning solution; adding curcumin to the polymer spinning solution; the mixed solvent is a mixture of chloroform and dibutanol; For step S1, this step uses poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) as raw materials to blend and form a polymer. Poly(3-hydroxybutyrate) (PHB) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) (PHO / PHD) are two different polyhydroxyalkanoates (PHA), which are polymerized by physical blending through melt blending; poly(3-hydroxybutyrate) is a short-chain length phase compound with high molecular weight, crystallinity and brittleness; poly(3-hydroxyoctanoate-co- Poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) are medium-chain aromatic hydrocarbons with high elasticity. Blending the two can complement each other and meet the dual requirements of strength and flexibility. Both poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) are biodegradable materials, which will not pollute the environment and can gradually degrade in the body, reducing the frequency of dressing changes while avoiding the risk of long-term retention in the body. Both have good biocompatibility, which makes it less likely to cause autoimmune reactions and allergic risks when used as dressings, which helps wound healing and has good safety.

[0026] At the same time, it is explained here that traditional wound dressings use non-degradable materials such as polyester fibers, which not only have poor air permeability, but also usually lack recycling - they are either incinerated or landfilled, which will also have a great impact on the environment. The present application hereby selects biodegradable and biocompatible raw materials from the source for the preparation of dressings, and considering that poly (3-hydroxyoctanoate-co-3-hydroxydecanoate) has a low glass transition temperature, which limits the spinnability and causes the fiber to be sticky and melted, increasing the difficulty of preparation in the later electrospinning process, it is blended with poly (3-hydroxybutyrate) with a high glass transition temperature to optimize the fiber molding process, so that it can produce fibers with better morphology and more stable performance in the subsequent electrospinning process, thereby meeting the dual requirements of wound dressings for material strength and flexibility.

[0027] The present application specifically selects a mixture of these two substances as raw materials. Compared with using only a single raw material, it can achieve complementary and enhanced material properties, and combine the advantages of the two to make the dressing more comprehensive in physical properties; it also makes the subsequent electrospinning processing more convenient; and more importantly, it can also improve the color change performance: broaden the color change range, that is, by adjusting the ratio between the two, the color change range and sensitivity of the fiber dressing can be regulated, so that the subsequent dressing can better respond and show different color changes in different environments; regulate the color change speed: although there are differences in the chemical structures of the two substances, their response speeds to color change stimuli are also different. By mixing the two, the color change speed can be optimized, so that the fiber dressing can change color quickly when needed, providing timely wound monitoring.

[0028] At the same time, in the present application, a mixed solvent is used to dissolve the polymer formed by poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) to ensure the dissolution effect of the two; and the mixed solvent uses chloroform and dibutanol as solvents, both of which are environmentally friendly and have high environmental adaptability during use and recycling.

[0029] S2: Electrospinning the polymer spinning solution to obtain a color-changing fiber dressing.

[0030] The entire preparation process of the present application has simple steps and strong operability. The prepared color-changing fiber dressing can change color with the degree of wound healing during wound care. At the same time, the nanofiber wound dressing is designed using bio-based polymers (i.e., PHA). The high polarity of PHA and the porosity of the fiber mesh will provide advantages such as easy and appropriate impregnation, odor suppression, therapeutic effect and easy removal of the dressing from the skin. The wound dressing with good biological activity and biocompatibility can not only reduce the impact on the environment, but also has significant antibacterial properties, which will greatly improve the combination of wound dressing products and provide a new and effective means for monitoring wound healing, with broad application prospects.

[0031] In one embodiment, in step S1, the mass ratio of poly(3-hydroxybutyrate) to poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) in the polymer is 1:(3-5); the volume ratio of chloroform to dibutanol in the mixed solvent is (7-10):3. In this embodiment, the focus is on controlling the mass of poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) in the polymer. Since there are some differences in the performance of the two, reasonable control of the mass ratio can balance the strength and toughness of the fiber; and a reasonable ratio can broaden the color change range of the color-changing fiber and improve the color change sensitivity.

[0032] For the mixed solvent, its main function is to promote the dissolution of poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate), uniformly disperse the polymer in the solvent, form a stable polymer solution, and make it have a high viscosity and appropriate fluidity, which is conducive to the formation of continuous fibers during the electrospinning process. Therefore, the reasonable control of the ratio of each substance in the mixed solvent can further optimize the dissolution of poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate), which will not be too high to cause the solution to be too viscous, nor too low to cause the polymer to be unable to be completely dissolved; and it can also further optimize the properties of the spinning solution, such as viscosity, surface tension, etc. These properties have an important influence on the formation and morphology of fibers during the electrospinning process.

[0033] In one embodiment, in step S1, the weight ratio of the curcumin to the polymer spinning solution is (1-10): 1. In this embodiment, the amount of curcumin added is associated with the polymer spinning solution. Since the performance of curcumin is unstable, it is easily disturbed by the external environment, which will lead to the problem of inaccurate color change. Therefore, this embodiment strictly controls the amount of curcumin added to control the corresponding sensitivity to factors such as environment and light, and ensure its stability; at the same time, as a color-changing dressing for medical use, its biocompatibility and safety are very important. Excessive use of curcumin may cause potential biological toxicity or allergic reactions, and its safety is guaranteed; and curcumin can improve certain mechanical properties of the fiber, such as tensile strength or toughness, to a certain extent, while ensuring its good color-changing performance, but excessive curcumin will cause the fiber performance to decline, affecting the final mechanical properties. Therefore, a proportional relationship is established between curcumin and the polymer spinning solution, which effectively ensures the smooth progress of the subsequent spinning process, obtains a fiber dressing with excellent mechanical properties, and can ensure the safety of the dressing and the accuracy of color change.

[0034] In one embodiment, the method further includes step S3: modifying the color-changing fiber dressing by using the AgNPs dip coating method to obtain a color-changing fiber dressing with antibacterial properties. In the AgNPs dip coating method, the color-changing fiber dressing is modified by the excellent antibacterial effect of silver nanoparticles, so that the color-changing fiber dressing has antibacterial properties to promote cell growth and accelerate wound healing, thereby making wound care more efficient and safe; at the same time, the AgNPs dip coating method utilizes the antibacterial properties of silver nanoparticles and the metal-enhanced singlet oxygen effect to enhance the singlet oxygen production of curcumin, thereby producing a synergistic antibacterial effect and improving the stability of curcumin, thereby ensuring the accuracy of color change monitoring. In addition, the AgNPs dip coating method is relatively simple to operate, does not require complex equipment and processes, and is suitable for industrial production.

[0035] In one embodiment, the AgNPs dip coating method specifically includes: using 4000ppm colloidal silver aqueous solution to dip coat the color-changing fiber dressing, the size of the nanosilver particles in the colloidal silver aqueous solution is 10-80nm; and the speed of taking out the color-changing fiber dressing from the colloidal silver aqueous solution is 170 mm / min. The size of the nanosilver particles directly affects its antibacterial performance and stability. Controlling the size can ensure that the particles have sufficient specific surface area and active sites, so as to exert the best antibacterial effect, and avoid the problem of excessively large particles causing a decrease in antibacterial performance or excessively small particles causing insufficient stability; and the dip coating speed is a key factor affecting the thickness and uniformity of the coating. Too fast a dip coating speed may cause the coating to be too thin, affecting the antibacterial effect; while too slow a dip coating speed may cause the coating to be too thick, increasing the cost and possibly affecting the air permeability and comfort of the dressing; therefore, the thickness and uniformity of the coating are accurately controlled by controlling the removal speed, so as to ensure that the antibacterial performance of the dressing meets the expected requirements.

[0036] In one embodiment, before performing step S2, the step further includes adding a LiBr solution after adding curcumin to the polymer spinning solution; and the amount of the LiBr solution added is 0.002 g / mL; it is explained here that 0.002 g / mL here means adding 0.002 g of LiBr solution to 1 mL of the polymer spinning solution according to the amount of the polymer spinning solution. The addition of the LiBr solution increases the conductivity of the entire polymer spinning solution, promotes charge transfer during subsequent electrostatic spinning, and improves the spinning efficiency; and the addition of the LiBr solution can make the electric field distribution of the polymer spinning solution more uniform, reduce the unstable factors in the spinning process, and then ensure the stability of the spinning.

[0037] In one embodiment, the parameters of the electrospinning process are set as follows: static voltage of 40-50 kV; static field environment temperature of 22±1.6°C, humidity of 38±2.1%, and injection speed of 0.2-0.8 mL / h. By controlling the static voltage, static field environment temperature, humidity, and injection speed, it is ensured that the produced fiber has good morphology, performance, and production efficiency.

[0038] A color-changing fiber dressing is prepared by the preparation method of the color-changing fiber dressing as described in any one of the above, and the color-changing fiber dressing has a thickness of 100-200 μm and a diameter of 300-2000 nm. The color-changing fiber dressing ensures its applicability and effectiveness in wound care; and has good bioactivity, biocompatibility, biodegradability, antibacterial and color-changing properties, providing a more effective and safe means for wound monitoring.

[0039] The present invention is further described below through specific implementation methods. Embodiment 1: A method for preparing a color-changing fiber dressing comprises the following steps: 3 mg of P(3HB) / P(3HO-co-3HD) was dissolved in a mixed solvent consisting of 0.7 mL of chloroform and 0.3 mL of dibutanol at a ratio of (1 / 3, w / w), and 3 mg of curcumin powder was added and mixed evenly to obtain a PHA spinning solution (i.e., a polymer spinning solution); electrospinning was performed using an electrospinning device under the conditions of a PHA spinning solution flow rate of 0.5 mL / h, a spinning voltage of 40 kV, and a receiving distance of 15 cm, and ultrafine fibers with a diameter of 300-2000 nm were collected, and a color-changing fiber dressing with a thickness of 100-2000 μm was obtained by accumulation; Meanwhile, as control group 1: 5wt% P(3HB) / P(3HO-co-3HD) (1 / 3, w / w) was dissolved in a mixed solvent consisting of 0.7mL chloroform and 0.3mL dibutanol, and 0mg curcumin powder was added and mixed evenly to prepare PHA spinning solution; electrospinning was performed under the conditions of a PHA spinning solution flow rate of 0.5mL / h, a spinning voltage of 40kV, and a receiving distance of 15cm, and ultrafine fibers with a diameter of 300-2000nm were collected, and a fiber dressing with a thickness of 100-2000μm was obtained by accumulation; As control group 2: 3 wt% P(3HB) was dissolved in a mixed solvent consisting of 0.7 mL chloroform and 0.3 mL dibutanol, and 3 mg curcumin powder was added and mixed evenly to prepare PHA spinning solution; electrospinning was performed under the conditions of a PHA spinning solution flow rate of 0.5 mL / h, a spinning voltage of 40 kV, and a receiving distance of 15 cm, and ultrafine fibers with a diameter of 300-2000 nm were collected, and a fiber dressing with a thickness of 100-2000 μm was obtained by stacking; As control group 3: 3 wt% P(3HO-co-3HD) was dissolved in a mixed solvent consisting of 0.7 mL chloroform and 0.3 mL dibutanol, and 3 mg curcumin powder was added and mixed evenly to prepare PHA spinning solution; electrospinning was performed under the conditions of a PHA spinning solution flow rate of 0.5 mL / h, a spinning voltage of 40 kV, and a receiving distance of 15 cm, and ultrafine fibers with a diameter of 300-2000 nm were collected, and a fiber dressing with a thickness of 100-2000 μm was obtained by stacking; It has been experimentally verified that the cell activity of the PHA fiber dressing prepared in this embodiment is greater than 90%. In an environment with a pH value of 5.5, 7.2 and 8.5, the color shows an evolution from light yellow to dark red, and the total color difference values ​​are 9, 38 and 57, respectively, which are significantly higher than the total color difference values ​​of comparison group 1 (1.9, 3.5 and 3.5), the total color difference values ​​of comparison group 2 (5, 20 and 31), and the total color difference values ​​of comparison group 3 (6, 20 and 31); when the total color difference of the material is greater than 5, the color change of the material can be recognized by the naked eye, and the larger the color difference value, the stronger its visibility.

[0040] Embodiment 2: A method for preparing a color-changing fiber dressing comprises the following steps: 3 mg P(3HB) / P(3HO-co-3HD) (1 / 3, w / w) was dissolved in a mixed solvent consisting of 0.7 mL chloroform and 0.3 mL dibutanol. At the same time, 3 mg curcumin powder was added and mixed evenly to obtain a PHA spinning solution. Under the conditions of a PHA spinning solution flow rate of 0.5 mL / h, a spinning voltage of 40 kV, and a receiving distance of 15 cm, electrospinning was performed by an electrospinning device to collect ultrafine fibers with a diameter of 300-2000 nm, and the color-changing fiber dressings with a thickness of 100-2000 μm were obtained by accumulation; Experimental verification shows that the cell activity of the PHA fiber dressing prepared in this example is greater than 90%. In environments with pH values ​​of 5.5, 7.2 and 8.5, the color changes from light yellow to dark red, and the total color difference values ​​are 18, 21 and 23, respectively.

[0041] Embodiment 3: A method for preparing a color-changing fiber dressing comprises the following steps: 3 mg P(3HB) / P(3HO-co-3HD) (1 / 3, w / w) was dissolved in a mixed solvent consisting of 0.7 mL chloroform and 0.3 mL dibutanol. At the same time, 5 mg curcumin powder was added and mixed evenly to obtain a PHA spinning solution. Electrospinning was performed under the conditions of a PHA spinning solution flow rate of 0.5 mL / h, a spinning voltage of 40 kV, and a receiving distance of 15 cm, and ultrafine fibers with a diameter of 300-2000 nm were collected and accumulated to obtain color-changing fiber dressings with a thickness of 100-2000 μm; Experimental verification shows that the cell activity of the PHA fiber dressing prepared in this example is greater than 90%. In environments with pH values ​​of 5.5, 7.2 and 8.5, the color changes from light yellow to reddish brown, and the total color difference values ​​are 20, 57 and 83, respectively.

[0042] Embodiment 4: A method for preparing a color-changing fiber dressing comprises the following steps: 3 mg P(3HB) / P(3HO-co-3HD) (1 / 3, w / w) was dissolved in a mixed solvent consisting of 0.7 mL chloroform and 0.3 mL dibutanol. At the same time, 10 mg curcumin powder was added and mixed evenly to obtain a PHA spinning solution. Electrospinning was performed under the conditions of a PHA spinning solution flow rate of 0.5 mL / h, a spinning voltage of 40 kV, and a receiving distance of 15 cm, and ultrafine fibers with a diameter of 300-2000 nm were collected and accumulated to obtain color-changing fiber dressings with a thickness of 100-2000 μm; Experimental verification shows that the cell activity of the PHA fiber dressing prepared in this example is greater than 90%. In environments with pH values ​​of 5.6, 7.2 and 8.5, the color changes from light yellow to reddish brown, and the total color difference values ​​are 51, 63 and 90, respectively.

[0043] from Figure 2It can be seen that with the increase of curcumin content in the fiber membrane, The value showed an increasing trend, especially in the pH range of 7.2-8.5. All of them are greater than 10.0, indicating the visibility of color change at different pH values. Under pH=8.5, PHA / nanosilver / curcumin fiber membrane with curcumin loading greater than 3wt% The value is greater than 60.0.

[0044] from Figure 3 It can be seen that the inventors of the present application studied the viability of human skin fibroblasts (NHDF) on PHA / nanosilver / curcumin films. From day 1 to day 3, the absorbance value of the PHA / nanosilver / curcumin film increased slightly, and during the 5-day culture period, there was no significant difference between PHA / nanosilver / curcumin 0, PHA / nanosilver / curcumin 1, PHA / nanosilver / curcumin 3, PHA / nanosilver / curcumin 5 and PHA / nanosilver / curcumin 10.

[0045] After setting the survival rate of the cells of the control group PHA / nanosilver / curcumin 0 film to 100%, the fiber film with curcumin added showed a slightly insignificant promotion effect on the survival of the cells after the first day of culture. With the extension of the culture time, on the third and fifth days, it can be seen that the cells have a small amount of apoptosis, which is due to the normal growth cycle of the cells. The cells of PHA / nanosilver / curcumin 3, PHA / nanosilver / curcumin 5 and PHA / nanosilver / curcumin 10 showed very high vitality. Throughout the experiment, we can see that the curcumin fiber films with different concentrations have no toxic side effects on cell survival.

[0046] The examples described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a color-changing fiber dressing, characterized in that: The following steps are involved: S1: dissolving a polymer formed by poly(3-hydroxybutyrate) and poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) in a mixed solvent to obtain a polymer spinning solution; adding curcumin to the polymer spinning solution; the mixed solvent is a mixture of chloroform and dibutanol; S2: Electrospinning the polymer spinning solution to obtain a color-changing fiber dressing.

2. The method for preparing a color-changing fiber dressing according to claim 1, characterized in that: In step S1, the mass ratio of poly(3-hydroxybutyrate) to poly(3-hydroxyoctanoate-co-3-hydroxydecanoate) in the polymer is 1:(3-5); and the volume ratio of chloroform to dibutanol in the mixed solvent is (7-10):

3.

3. The method for preparing a color-changing fiber dressing according to claim 1 or 2, characterized in that: In step S1, the weight ratio of the curcumin to the polymer spinning solution is (1-10):

1.

4. The method for preparing a color-changing fiber dressing according to claim 1, characterized in that: The method also includes step S3: modifying the color-changing fiber dressing by using the AgNPs dipping method to obtain the color-changing fiber dressing with antibacterial properties.

5. The method for preparing a color-changing fiber dressing according to claim 4, characterized in that: The AgNPs dip coating method specifically includes: using a 4000ppm colloidal silver aqueous solution to dip coat the color-changing fiber dressing for modification, wherein the size of the nanosilver particles in the colloidal silver aqueous solution is 10-80nm; and the speed of taking the color-changing fiber dressing out of the colloidal silver aqueous solution is 170 mm / min.

6. A method for preparing a color-changing fiber dressing according to claim 1 or 4, characterized in that: Before performing step S2, the method further includes adding LiBr solution after adding curcumin to the polymer spinning solution; and the added amount of the LiBr solution is 0.002 g / mL.

7. The method for preparing a color-changing fiber dressing according to claim 1, characterized in that: In step S2, the parameters of the electrospinning process are set as follows: the electrostatic voltage is 40-50 kV; the electrostatic field environment temperature is 22±1.6°C, the humidity is 38±2.1%, and the injection speed is 0.2-0.8 mL / h.

8. A color-changing fiber dressing, characterized in that: The color-changing fiber dressing is prepared by the preparation method of the color-changing fiber dressing according to any one of claims 1 to 7, and the color-changing fiber dressing has a thickness of 100-200 μm and a diameter of 300-2000 nm.

Citation Information

Patent Citations

  • PH-sensitive chronic wound medical dressing with one-way liquid guide function and preparation method of pH-sensitive chronic wound medical dressing

    CN116459381A

  • Nano-silver / dual-modified chitosan antibacterial hydrogel dressing for indicating wound infection condition through color change effect and preparation method of nano-silver / dual-modified chitosan antibacterial hydrogel dressing

    CN113975458A

  • Gelatin / polyester fiber dressing and preparation method thereof

    CN115645592A

  • Application of composite nanofiber membrane in preparation of medicine for promoting healing of diabetic wound

    CN116270555A

  • Biodegradable plant wound dressing composed of electrospun nanofibers

    US20160219874A1